Reluctant duchess - White, Roseanna M. (White, Roseanna M., Ladies of the manor., 2016)
After a shocking attack, heiress Rowena Kinnaird feels betrayed by her family and the man she was to marry. She flees the Highlands, landing at the Duke of Nottingham's door. Rowena needs help but is hesitant to trust a flirt like Brice. Then she learns his life is also under threat. When her father locates her, can she and Brice find a way out of danger?